Different perceptions of interprofessional collaboration and factors influencing the one-stop service for sexual assault victims in Taiwan. Issue 1 (2nd January 2017) - Tien, Lih-Chu; Wu, Yi-Ling; Lin, Tsai-Wen; Wang, Samuel Shih-Chih
ABSTRACT: The purpose of interprofessional collaboration is to bring better services for sexual assault victims. In order to avoid secondary victimisation and improve the quality of forensic examination and prosecution rate, a one-stop service has been developed recently in Taiwan. However, whether the collaboration is successful may depend on participants' professional backgrounds and personal experiences and can be influenced by a number of factors. This study used the Index of Interdisciplinary Collaboration to examine the different perceptions of collaboration in team members and the related influences on collaboration. Surveys were conducted in 140 team members including social workers, doctors, nurses, and police officers. The result indicated that collaboration was perceived differently in different professionals and significantly lower by social workers in the domain of interdependence and reflection on process. Factors such as professional roles, structural characteristics, personal characteristics, and history of collaboration were positively associated with the overall perception of collaboration. Only structural and personal characteristics predicted the type of profession. This study highlights the importance to acknowledge different experiences. Additional efforts and investments for improving mutual help and trust by the organisations are recommended.